Provision of immediate postpartum contraception to women living with HIV in the Eastern Cape, South Africa; a cross-sectional analysis - Oladele Vincent Adeniyi; Anthony Idowu Ajayi; Oluwaseyi Dolapo Somefun; John Shearer Lambert (BMC, 2020)
Abstract Background Universal access to contraception is an important strategy adopted by the South African government to reduce the high rate of unintended pregnancies, especially in women living with HIV. In this article, we describe the choices of contraception and also, examine the influencing factors of the choices of contraception in the immediate postpartum period in parturient women with HIV in the Eastern Cape, South Africa. Methods In this prospective cross-sectional study, 1617 parturient women with HIV completed a survey on the choice of contraception received in the immediate postpartum period (within 72 h) across three large maternity services in the Eastern Cape between September 2015 to May 2016. Additional information was extracted from their medical records. Choices of contraception were categorised as; short-acting (injectables), long-acting reversible (intrauterine device and implants) and permanent contraception (tubal ligation). Adjusted and unadjusted logistic regression models were employed to determine the influencing factors of the choices of contraception received by the cohort. Results Participants were predominantly single (69.1%), unemployed (75.1%), had a grade 7-12 level of education (88.4%) and were HIV positive before their index pregnancy (81.3%). The prevalence of immediate postpartum contraception was high (n = 1507; 93.2%) with Injectables being the preferred choice in the majority of the participants (n = 1218; 75.3%). After controlling for all relevant covariates, single marital status was associated with a higher likelihood of immediate postpartum contraceptive initiation (AOR; 1.82 95% CI 1.10-3.03). Overall, women were more likely to initiate a long-acting reversible and irreversible methods when older than 35 years and having had more than two children. Conclusions We found a high prevalence of immediate postpartum contraception with a preference for Injectables in the study setting. Long-term monitoring of this cohort will elucidate on contraceptive discontinuation and risk of unintended pregnancies in the region. Plain English Summary Ensuring universal access to contraceptives is an important strategy to reduce the rate of unintended pregnancies at the population level. This strategy was adopted by the South African government with a vision of stemming the tide of unintended pregnancies among women living with HIV. In this study, the choices of contraception adopted by women living with HIV following the delivery of their babies were explored. In addition, the study highlights the factors that predict these choices. Participants were asked the choice of contraception they had received prior to being discharged from the maternity centres where they had delivered their babies. The various types of contraception were then categorised by their duration of action. Three distinct groups emerged; short-acting injectables, long acting reversible contraceptives and permanent methods. Of the 1617 women included in the study, 1117 were single and 1314 knew their HIV status prior to the onset of the index pregnancy. Almost all the women (1507 out of 1617) received one form of contraception before leaving the hospital. Many women (1218 out of 1617) chose injectable contraception (short-acting contraception) over the other types of contraception. Women who were older than 34 years and who had three or more children were more likely to choose a long-acting reversible contraceptive and permanent method over the short-acting contraception or nothing. In conclusion, given the short duration of action of the predominant method adopted by these women, a long-term follow up of the study participants will provide more information on the continued use of contraception and risk for unintended pregnancies.